Combined Technique and Its Clinical and Pathogenetic Evaluation in Treatment of Central Serous Chorioretinopathy Using Subthreshold Microimpulse Laser Irradiation with a Wavelength of 577 nm in Combination with Injections of Platelet Autoplasma - O. M. Stanishevskaya; V. V. Chernykh; V. I. Bratko (Acta Biomedica Scientifica)
Background. Lack of a holistic understanding of the etiology and pathogenesis of central serous chorioretinopathy (CSH), which determines the conduct of pathogenetic therapy, as well as the lack of effectiveness of treatment methods aimed at developing new pathology methods.Aims. To conduct a comparative therapeutic potential of a combination of subthreshold micropulse laser irradiation (SMILV) with a course of injection of autologous plasma enriched with platelets (TP) in CSH. To evaluate the effectiveness of SMILV with a wavelength of 577 nm with wing-injection injections of TP compared with SMIV monotherapy in the treatment of CSH. Consider issues of modern treatment of CSH, as well as determine the levels of cytokines in the tear fluid of patients with CSH before and after SMILV and SMILV + TP treatment.Methods and methods. The study was conducted on 60 patients (60 eyes) with CSH. Patients were divided into 2 groups: in the comparison group, patients received treatment only SMILV wavelength 577 nm, and in the experimental group – SMILV followed by the introduction of TP. TP was prescribed after 72 hours, 3 injections in the region of the pterygomaxillary fossa on the side of damage to the eyes, with an interval between injections of 72 hours.SMILV was performed on a Supra 577 nm laser machine (Quantel Medical, France) over the entire area of macular edema. Conclusion. Comparative analysis of clinical and functional results of treatment of central serous chorioretinopathy SMILV with a wavelength of 577 nm and a combination of SMILV with injections of autologous plasma enriched with platelets and the outcome of the disease revealed a greater effectiveness of combining SMILV with a course of injections of autologous plasma enriched with platelets.